GAME DEVELOPMENT "ATTACK OF KRONA" AS A MEDIA CAMPAIGN FOR THE ADAPTATION OF NEW HABITS - Sudi Anggara, I Gede Adi; Jayanegara, I Nyoman; Adi Putra Yasa, I Wayan; Agung Pandawana, I Dewa Gede; Setiawan, I Ketut (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2022)
The pandemic due to infection with the new Corona virus (COVID-19) has swept the world over the past year. Reporting about this in various media causes anxiety or panic in the community which in turn can cause psychosomatic symptoms. This symptom can be overcome with a diversion technique that is doing everything you like. Other than that, the application of health protocols must be carried out to suppress the spread of COVID-19 cases. Education regarding to the health protocols needs to be carried out continuously by utilizing new media that can also overcome psychosomatic symptoms. Game is one form of new media. Game Attack of The Krona is a creative education about health protocols designed with the design thinking method. This game is a platformer concept consisting of 4 level Education about health protocols will be part of the game so that education can be done easily, interestingly and fun. This game has passed blackbox testing regarding the functionality of the application and the sharpness of the image display on various smartphone devices. By playing this game, information can be carried out, so that behavior changes with the implementation of health protocols can become a habit in preventing various diseases in the future.